2007
DOI: 10.1179/016164107x204729
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of capillary VEGF isoforms following traumatic brain injury

Abstract: These results show a distinct expression pattern of angiogenic factors following injury and suggest that pericyte involvement in adaptive angiogenesis may be altered following TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 53 publications
1
32
0
1
Order By: Relevance
“…Previously, we have shown that pericytes are highly responsive to low O 2 levels [10, 22, 27]. As early as one hour following exposure to low O 2, pericytes undergo changes in eicosanoid repertoire [22] and mount a HIF-1 response [22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we have shown that pericytes are highly responsive to low O 2 levels [10, 22, 27]. As early as one hour following exposure to low O 2, pericytes undergo changes in eicosanoid repertoire [22] and mount a HIF-1 response [22].…”
Section: Resultsmentioning
confidence: 99%
“…VEGF directly induces the proliferation and migration of pericytes under hypoxic conditions and also indirectly regulates pericyte recruitment via endothelial cell production of nitric oxide (NO) [46]. Pericytes constitutively express VEGF mRNA but transcripts are not translated until after the hypoxic stimulus [10, 27]. For this gene, a group of candidate regulatory microRNAs have been identified recently in tumor cells [12, 52] and human monocytes [53, 54].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies in cats have shown that brain pericytes migrate away from capillaries rapidly following a hypoxic insult 120 and pericyte-endothelial cell ratio in brain is reduced one week following hypobaric hypoxia in rodents 121 . During hypoxia, VEGF levels are upregulated in pericytes within 24 hours and upregulated in astrocytes after 4 days 121 .…”
Section: Pericyte-endothelial Signal Transductionmentioning
confidence: 99%
“…During hypoxia, VEGF levels are upregulated in pericytes within 24 hours and upregulated in astrocytes after 4 days 121 . Inhibiting VEGF in chronic mild hypoxia (1% O 2 ) promotes angiopoietin-1 (Ang1)-mediated endothelial cell tight junction stabilization, whereas severe hypoxia (0.1% O 2 ) promotes apoptosis of endothelial cells, as shown in in vitro endothelial and pericyte co-cultures 122 .…”
Section: Pericyte-endothelial Signal Transductionmentioning
confidence: 99%
“…VEGF is expressed in the CNS after experimental trauma and stroke [134,135,136] and has important implications in mediating ectopic migration of SVZ neuroblasts to the site of injury. Wang et al [137] showed that VEGF-overexpressing mice had enhanced SVZ cell proliferation after permanent focal cerebral ischemia, with chains of migratory neuroblasts extending from the SVZ to the peri-infarct cortex, leading to an ultimate increase in the number of newly generated cortical neurons at 14–28 days.…”
Section: Injury-induced Factors Mediating Redirected Migration To Dammentioning
confidence: 99%